Seize and hold : master strokes on the battlefield - Perrett, Bryan (London : Arms and Armour ; New York, NY : Sterling Pub. Co. [distributor], 1995)
This volume recounts eleven prime examples of "coup de main" military strategy from the 20th century, including both World Wars, Vietnam and Korea. The author covers a selection of classic armed coup de main where small but powerful forces have been tasked with getting to, seizing and holding until relieved important local and strategic objectives. These sudden and swiftly organized and executed moves can either come from the initiative of troops on the battlefield in the heat of battle, or via prior recognition of a forthcoming opportunity. Topics include Balkin mountain action in 1916, the assault on Belgium 1940, Beda Fomm, Meiktila in Burma, Remagen Bridge, Korea and Ia Drang in Vietnam.
Opening the iron gate -- Young Mister Rommel -- Polish eagle and Russian bear -- The third dimension : Holland and Belgium 1940 -- The road to Beda Fomm -- Deep strike : Jitra and Slim River, Malaya 1941-2 -- Hill 309 and the bridge at 637436 -- Meiktila -- the master stroke -- Taken at a run : the capture of the Ludendorff Bridge at Remagen, March 1945 -- Going for the jugular : the Inchon landings, September 1950 -- Earthquake on Chu Pong : the La Drang Valley campaign, Vietnam 1965 -- Postscript : the coup comes of age.
Includes bibliographical references (pages 215-216) and index.
Keywords: Battles; Military history, Modern; battles; Battles; Military history, Modern; war fiction